Specific lung mucosal and systemic immune responses after oral immunization of mice with Salmonella typhimurium aroA, Salmonella typhi Ty21a, and invasive Escherichia coli expressing recombinant pertussis toxin S1 subunit. - Walker, M J (1992)
Pertussis toxin (PT) is considered an essential protective component for incorporation into new generation vaccines against Bordetella pertussis, the causative agent of whooping cough. Traditionally, antipertussis vaccination has employed an intramuscular route. An alternative to this approach is to stimulate mucosal and systemic immune responses by oral immunization with live vaccine carrier strains of Salmonella spp. or Escherichia coli. Recombinant S1 subunit of pertussis toxin was expressed in the attenuated aroA mutant of Salmonella typhimurium, SL3261, in the human typhoid vaccine strain Salmonella typhi Ty21a, and in E. coli CAG629 containing the Shigella flexneri plasmid pWR110, which encodes bacterial invasiveness of epithelial cells. Expression of recombinant PT S1 subunit (rPT-S1) did not affect in vitro invasiveness of the tested strains, which retained the ability to adhere to and invade the embryonic human intestinal cell line HI-407. Following oral immunization of mice with the live vaccine strains expressing rPT-S1, immunoglobulin G (IgG), IgA, and IgM responses were monitored. IgG specific to PT was detected in serum samples of mice, while IgG and IgA specific to PT were detected in lung washes after oral immunization with living Salmonella spp. or E. coli (pWR110) expressing rPT-S1. Utilization of live oral vaccines expressing B. pertussis antigens, which stimulate both a systemic and lung mucosal response, may provide an attractive alternative to purified component vaccines against whooping cough.